PENGARUH IKLIM KELAS TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMAN3 TANJUNG RAJA - Dewi Permata Sari; Rusmin AR; Deskoni Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This Studi aims to determine the Influence of Climate Class on Student Learning Motivation on the Subject of Economics in SMA Negeri 3 Tanjung Raja. This research uses quantitative approach with type of associative research. The population of this research is all of class X in SMA Negeri 3 Tanjung Raja. The sample was determined using cluster random sampling. Data collection techniques used questionnaires with likert scale model. Technique of data analysis using simple linier reqression obtained Fcount ≥ from Ftabel that so Ho rejected and Ha accepted , then with product moment correlation test got value r = 0,3786 with enough influence category. The determinant coefficient shows the contribution of class climate to the learners motivation of 14,01% the rest is influenced by other factors or variables, and it can be concluded the relationship between the two variables is significant. So, it is advisable for the school and especially teachers economic subjects to be able to create a conducive class climate and comfortable so that learners feel calm and comfortable to learm it aims to improve motivation learners learners.